2005
DOI: 10.1038/sj.onc.1208859
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional BRCA1 is only indirectly linked to multiple centrosomes

Abstract: A remarkable and yet unexplained phenomenon in cancer cells is the presence of multiple centrosomes, organelles required for normal cell division. Previously, it was demonstrated that the tumor suppressor BRCA1 is a component of centrosomes. This observation led to the hypothesis that defective BRCA1 results in malfunctioning centrosomes and faulty centrosomes are a possible cause of cancer. Using EGFP-tagged fusion proteins and BRCA1 À/À cells we show that although some BRCA1 antibodies do label centrosomes u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 22 publications
0
14
1
Order By: Relevance
“…Likewise, the reported Cep63-dependent presence of Cdk1 at centrosomes [138] is almost certainly due to antibody cross-reactivity with Cep152 [139]. Thus, when interpreting immunocytochemical data reporting on unexpected centrosome-associations of particular proteins, it would seem wise to consider carefully the possibility of antibody-related artefacts [135,137,139,140]. Not only have proteins with well-established functions in DNA damage response pathways been reported to reside at centrosomes, but the opposite is also true: genuine centrosomal proteins have been implicated in DNA damage response.…”
Section: Centrosomes As Signalling Platforms In Vertebrates? (A) Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the reported Cep63-dependent presence of Cdk1 at centrosomes [138] is almost certainly due to antibody cross-reactivity with Cep152 [139]. Thus, when interpreting immunocytochemical data reporting on unexpected centrosome-associations of particular proteins, it would seem wise to consider carefully the possibility of antibody-related artefacts [135,137,139,140]. Not only have proteins with well-established functions in DNA damage response pathways been reported to reside at centrosomes, but the opposite is also true: genuine centrosomal proteins have been implicated in DNA damage response.…”
Section: Centrosomes As Signalling Platforms In Vertebrates? (A) Cellmentioning
confidence: 99%
“…Moreover, APC/C activity was shown to oscillate, leading to successive rounds of Cdk2 and separase activation in the arrested cells [161]. Although centrosome amplification does not necessarily require passage through mitosis [159], we emphasize that supernumerary centrosomes are expected to arise whenever cells with damaged DNA fail to arrest at the G2/M checkpoint and then advance to abortive divisions [16,140]. The physiological significance of centrosomal responses to DNA damage remains to be fully understood, but the possibility has been raised that centrosome fragmentation or amplification may constitute a safeguard mechanism to kill cells with DNA damage via induction of division failures [156,159].…”
Section: Centrosomes As Signalling Platforms In Vertebrates? (A) Cellmentioning
confidence: 99%
“…Because BRCA1 localizes to centrosomes at all phases of the cell cycle (5), it is likely that the BRCA1 ubiquitin ligase activity is directly involved in regulating centrosome function. Although BRCA1 localization to the centrosome was questioned in one study in which the green fluorescent protein fusion of BRCA1 failed to localize to the centrosome (17), a number of other reports have shown endogenous BRCA1 localization to the centrosome (4,5,18,19).…”
Section: Introductionmentioning
confidence: 99%
“…However, centrosomal localization of BRCA1 was later challenged by one group: through the examination of exogenously introduced fluorescent protein-tagged BRCA1, they have concluded that BRCA1 does not localize to centrosomes. 30 The question of whether BRCA1 localizes to centrosomes had not been resolved. Here, we undertook a rigorous analysis of centrosome localization of BRCA1.…”
Section: Introductionmentioning
confidence: 99%